A Self-Inflating Bag May Cause Hypocapnia in a Rabbit Model of Manual Ventilation Compared to the T-piece Resuscitator - Haddad, Luciana B.; Mascaretti, Renata S.; Valle, Luciana A. P. A.; Rebello, Celso M. (American Journal of Perinatology, 2017)
Background Manual ventilation is a key aspect that determines the efficiency of neonatal resuscitation and may be performed by specialists using different equipment and professionals.Objective To compare manual ventilation using T-piece resuscitator and self-inflating bag in an experimental model, with regard to gasometric and respiratory mechanical parameters.Methods Adult rabbits were submitted to 10 minutes of ventilation with each device operated by three groups of volunteers: physicians, physiotherapists, and nurses. We measured respiratory mechanics throughout the study as well as blood gas before and after ventilation, and we compared professionals' performance on each device.Results Compared with T-piece, animals ventilated with the self-inflating bag in the nurse group (n = 7) presented a greater minute volume (390 ± 108 vs. 766 ± 410 mL/min, p < 0.05) relative to the physiotherapist group (n = 7, 418 ± 192 vs. 886 ± 787 mL/min), and physician group (n = 7, 438 ± 206 vs. 705 ± 434 mL/min); similar results were found in the nurse, physiotherapist, and physician groups for respiratory alkalosis (7.40 ± 0.11 vs. 7.61 ± 0.02, p < 0.05; 7.37 ± 0.10 vs. 7.52 ± 0.23; and 7.36 ± 0.07 vs. 7.40 ± 0.18 mL/min, respectively), and hypocapnia (32.4 ± 6.9 vs. 23.4 ± 7.5 mm Hg, p < 0.05; 40.4 ± 10.8 vs. 28.0 ± 15.2 mm Hg; and 38.0 ± 13.8 vs. 42.6 ± 18.1 mm Hg, respectively).Conclusion Self-inflating bag resulted in hypocapnia and respiratory alkalosis in the nurse group, and ventilation using a T-piece resulted in a lower tidal and minute volume.
Keywords: ventilation; positive-pressure ventilation; infant; newborn